Theoretical and experimental investigation of the evacuated tube solar water heater system - Phrut Sakulchangsatjatai (2020)
© 2020 Society of Thermal Engineers of Serbia. In this study, the evacuated tube solar water heater system using thermosyphon has been investigated experimentally as well as theoretically. Solar radiation and ambient temperature data from Chiang Mai province were used for the modelling system by explicit finite difference method. The effects of thermosyphon diameters and number of evacuated tubes on the net saving of solar water heater system were analyzed. The mathematical results showed that the optimal number of evacuated tubes and thermosyphon diameter occurs at eight evacuated tubes, which are 15.88 mm of evaporator diameter and 22.22 mm of condenser diameter under personal hygiene conditions. The solar water heater system at optimal parameters was constructed and tested for the system prototype. The theoretical results were validated by the experimental results. It was found that the theoretical results can be used to predict temperature, heat transfer rate, and thermal efficiency to show good agreement with the experimental results as well as previous research. The experimental and theoretical results showed that the maximum temperature for hot water was 65.25 °C and 71.66 °C, respectively. Moreover, the thermal efficiency of the system based on the theoretical result was 60.11%, with relative error being about 3.04% of the experimental result.